The performance of attached and suspended growth process in integrated fixed activated sludge - Mohiyaden H.A.; Sidek L.M.; Hayder G. (Taylor's University, 2023)
River Water Treatment Plants (RWTPs) have been constructed along Klang River and its tributaries under River of Life Project (ROL) to upgrade urban River water quality. RWTPs apply Integrated Fixed-Film Activated Sludge (IFAS) system in biological process to treat polluted Klang Rivers and its tributaries. This system is based on the activity of attached growth biomedia and often defined by the content suspended growth biomedia. Hence, suspended biomass activity is usually not been evaluated, however, it is neglected. Therefore, this paper is to evaluate the biomass content, the following parameters have been used; Mixed Liquor Volatile Suspended Solids (MLVSS) for expressing the suspended growth system and Total Volatile Solids (TVS) for expressing the attached growth system. MLVSS content for all RWTPs was found very low due to dilution from rainwater since Klang River experienced several high intensity rainfall events. From total 6 RWTP stations have been monitored, RWTP Sg. Kemensah, RWTP Sg. Sering and RWTP Sg. Gisir have showed low amount of biomass in the oxidation chamber due to low organic loading and matured biofilm formation in RWTP Gisir. On the other hand, RWTP Sg. Belongkong and RWTP Sg. Kemunsing showed satisfactory biomass growth. For RWTPs, the biological treatment process involving attached growth system are considered the best option as compared to suspended growth. It has been shown that under ROL project, all RWTPs are able to remove a large number of contamination despite of their low MLVSS content (0.2-50 mg/L) and low loading influent capacity (10-30 mg BOD/L). In addition, it has been noticed that low hydraulic retention time (2 hours) and low aeration rate (5.0-7.0 L/min) are the factors that can ensure an effective biofilm growth and total reduction of pollutants in RWTP. These process factors may be an interesting subject to be addressed in further research topics, starting from the results of this paper. This paper will present the introductory and amount of hybrid growth system in IFAS process including attached and suspended growth process. School of Engineering, Taylors University.